Genre-Based Instruction the Key ESP Solution for Adult Learning in Professional Settings - Nesba, Asma (University of eloued جامعة الوادي, 2017)
The present research aims at highlighting the importance of introducing the genre- based approach as an English for Specific Purposes (ESP) solution to speed up the mastery of the English language- related activities in the workplace. Business is considered as the most important field which requires English in Algeria. However, workers in this domain encounter difficulties to accomplish English language- related activities. They fail to explore their previous English language to meet the workplace needs. Even general English instruction was not beneficial for them. A Triangulated study was then conducted on a group of ten adult learners working in the field of business. A Genre-Based instruction was adopted in order to equip them with the required English language skills that enable them to master the different genres that constitute the business correspondence, mainly writing both ordinary and electronic letters (e-mails). Three data gathering tools were used.First, needs analysis method was used adopting Hutchinson and Waters' (1987) approach to NA to find relevant information about the most likely encountred genres in their professional settings. Secondly, an intensive genre- based instruction in the form of desgined task- based activities over a period of two months at a rate of three two-hour sessions per week was followed. Different types of business e-mails with different communicative purposes were dealt with. In this phase the « Teaching-Learning Cycle » of Feez (1998) is used. Moves analysis' tasks, based on identifying the rhetorical movesof a specific genre were also used.Finally a post instructional questionnaire was used to elicit the learners' attitudes towards the genre-based instruction.Results of the present study suggest that the genre- based instruction is an efficient method to enhance the English language writing perfornace of adult learners. It helps in raising the awareness of the learners towards genre. The results also come to prove the importance of needs analysis in designing suitable ESP courses. The learners' attitudes towards genre- based instruction are positive since they can meet the the workplace language needs.Results led to the construction of recommendations that focus on adopting the genre -based instruction as an ESP solution to promote mainly adult leraners in the professional settings.
IV International Eurasian Educational Research Congress « Changing Times, Changing Needs : Online Education, Equality, Immigration, Diversity, Concluding Remark »» Pamukkale University / DENIZLI / TURKEY
Keywords: Adult Learning, EOP, ESP, Genre, Genre-based Instruction